Fetal Mediastinal Fibrosarcoma. Report of Two Cases. (3rd September 2022) - Cagan, Murat; Yildirim, Selma; Turkmen, Gulenay Gencosmanoglu; Ozyuncu, Ozgur; Akcoren, Zuhal; Deren, Ozgur; Gucer, Safak
Abstract: Introduction: One-third of fetal soft tissue tumors are malignant and include congenital fibrosarcoma (CF). We report two fetal CFs arising in the posterior mediastinum. Case Presentation: In case 1, the CF resulted in a mediastinal shift, extensive infiltration of the tumor around adjacent structures, pulmonary hypoplasia, pleural effusion, and rapid growth. The pregnancy was terminated. Case 2 had multiple intrathoracic masses, thoracic hypoplasia, pleural effusion, and fetal death. Both were diagnosed as fibrosarcoma at fetopsy. Discussion: Although congenital CF tends to be locally aggressive with a low metastatic rate, it tends to grow rapidly and the tumor location can affect fetal survival. In Case 1, the tumor demonstrated locally aggressive behavior whereas multiple distant metastases such as lung, liver, adrenals, and left eye were detected in Case 2. The tumor was directly responsible for intrauterine fetal demise in the second case.